Systematic of Albian - Cenomanian Gastropods and Bivalves from the Kazhdumi Formation, Zagros Basin - I. Maghfouri Moghaddam; P. Shams; M. Parvaneh Nejad Shirazi (Journal of Sciences, Islamic Republic of Iran)
The Albian- Cenomanian (Kazhdumi Formation) sediments from northeast of Shiraz, Zagros Basin, represents a carbonate sedimentary succession and contain diverse gastropods and bivalves. Detailed studies on 80 samples of invertebrate macrofauna on two stratigraphic sections led to recognized 2 species and 5 genera of gastropods and 7 species and 13 genera of bivalves assemblages. The abscence of large gastropods and bivalves fauna and abundance of suspension-feeders indicated instability of the substrate and a  medium enrgy condition. From a palaeobiogeographic point of view, the fauna from the Kazhdumi Formation were similar to the Central Iran and North Jordan and Wadi Qena (Egypt).